1991
DOI: 10.2337/diab.40.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IP3, Spermine, and Mg2+ on Regulation of Ca2+ Transport by Endoplasmic Reticulum and Mitochondria in Permeabilized Pancreatic Islets

Abstract: Inositol 1,4,5-trisphosphate (IP3) increased the free-Ca2+ concentration in the incubation medium of permeabilized ob/ob mouse pancreatic islets. Spermine decreased the free-Ca2+ concentration through stimulation of mitochondrial Ca2+ uptake and attenuated the effect of IP3. Mg2+ antagonized the effects of spermine, thereby increasing the free-Ca2+ concentration and enhancing the effect of IP3 on the free-Ca2+ concentration. Because IP3 releases Ca2+ from endoplasmic reticulum, these results indicate that endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…IP 3 is known to mobilize Ca 2+ by binding to receptors on the endoplasmic reticulum or a portion thereof (44,45). Intracellular effects of IP 3 have previously been studied in subcellular fractions of rat insulinoma cells (42), in various permeabilized insulin-secreting cell lines (13)(14)(15)(16), permeabilized islets (10,11,46), and islet cells (12,13). In the present study, individual (3-cells were analyzed with regard to the action of IP 3 on Ca 2+ sequestered in the organelles.…”
Section: Fig 6 Effects Of Mitochondrial Inhibition On Organelle Ca mentioning
confidence: 99%
See 1 more Smart Citation
“…IP 3 is known to mobilize Ca 2+ by binding to receptors on the endoplasmic reticulum or a portion thereof (44,45). Intracellular effects of IP 3 have previously been studied in subcellular fractions of rat insulinoma cells (42), in various permeabilized insulin-secreting cell lines (13)(14)(15)(16), permeabilized islets (10,11,46), and islet cells (12,13). In the present study, individual (3-cells were analyzed with regard to the action of IP 3 on Ca 2+ sequestered in the organelles.…”
Section: Fig 6 Effects Of Mitochondrial Inhibition On Organelle Ca mentioning
confidence: 99%
“…So far, intracellular Ca 2+ stores have been characterized after permeabilization of islets (10,11), islet cells (12,13), or insulinsecreting cell lines (13)(14)(15)(16) using extracellular fluorescent indicators, microelectrodes, or radiotracer methods. However, these techniques cannot be applied to individual cells.…”
mentioning
confidence: 99%
“…Taken together these results implicate that SP affects intracellular Ca 2+ release at a step between G‐protein activation and the formation of IP 3 . Spermine has been shown to increase Ca 2+ uptake in heart, liver and brain mitochondria, suggesting that SP affects cytosolic [Ca 2+ ] also via this mechanism (Lenzen & Rustenbeck 1991, Lenzen et al . 1992, Rustenbeck et al .…”
Section: Intracellular Ca2+ Release and Uptakementioning
confidence: 99%
“…More recently, the effects of spermine on mitochondrial Ca2+ transport have attracted considerable attention. However, although an early study by Akerman (1977) described an inhibition of mitochondrial Ca2+ uptake by spermine, many subsequent studies reported a stimulatory effect of spermine on Ca2+ uptake by mitochondria from liver (Nicchitta & Williamson, 1984;Lenzen et al, 1986;Kroner, 1988;McCormack, 1989), hepatoma cells (Fiskum, 1985), brain (Lenzen et al, 1986;Jensen et al, 1987Jensen et al, , 1989Rottenberg & Marbach, 1990), heart (Lenzen et al, 1986;McCormack, 1989), kidney (McCormack, 1989) and pancreatic islets (Lenzen & Rustenbeck, 1991). Surprisingly, however, for unknown reasons rather different half-maximally effective concentrations were reported (Nicchitta & Williamson, 1984;Lenzen et al, 1986;Jensen et al, 1987;Kroner, 1988;McCormack, 1989).…”
Section: Introductionmentioning
confidence: 99%